2023
DOI: 10.3389/fnmol.2023.1099256
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in spinal cord injury: A narrative review

Abstract: Spinal cord injury (SCI) is a global medical problem with high disability and mortality rates. At present, the diagnosis and treatment of SCI are still lacking. Spinal cord injury has a complex etiology, lack of diagnostic methods, poor treatment effect and other problems, which lead to the difficulty of spinal cord regeneration and repair, and poor functional recovery. Recent studies have shown that gene expression plays an important role in the regulation of SCI repair. MicroRNAs (miRNAs) are non-coding RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…In addition, some studies have reported that by regulating the TUG1/miR-214/HSP27 signaling pathway, the proportion of Treg cells can be reduced, thereby alleviating acute SCI (125). Treg cells can also regulate neuroendocrine circuits by inhibiting cytokine secretion and release; therefore, regulating neuronal activity Janyga et al, 2023 1 . Treg cells downregulate TNF-a and IL-6 expression in microglia by inhibiting STAT3 pathway activation, which ultimately improves the damaged spinal cord microenvironment and promotes the recovery of neurological function after SCI (126).…”
Section: Treg Cell Regulation Of the Inflammatory Response After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies have reported that by regulating the TUG1/miR-214/HSP27 signaling pathway, the proportion of Treg cells can be reduced, thereby alleviating acute SCI (125). Treg cells can also regulate neuroendocrine circuits by inhibiting cytokine secretion and release; therefore, regulating neuronal activity Janyga et al, 2023 1 . Treg cells downregulate TNF-a and IL-6 expression in microglia by inhibiting STAT3 pathway activation, which ultimately improves the damaged spinal cord microenvironment and promotes the recovery of neurological function after SCI (126).…”
Section: Treg Cell Regulation Of the Inflammatory Response After Scimentioning
confidence: 99%
“…Spinal cord injury (SCI) occurs when there is injury or damage to the spinal cord due to an external force that may result in neurological dysfunction. This injury can affect, to varying degrees, the sensory, motor, and autonomic functions of the body ( 1 ). Such injuries result in severe deterioration in the quality of life of patients and increase disability and mortality rates for spinal cord injuries ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include miR-873a-5p, which inhibits inflammation and enhances anti-inflammatory cytokine release, and miR-133b and miR-124, which reduce proinflammatory factors and inflammation in neurodegenerative conditions [86]. Other miRNAs, such as miR-100, miR-183, miR-23b, miR-34a, miR-150, miR-27a, miR-340-5p, miR-193a, miR-429, and miR-223-5p, also show potential in attenuating inflammation, oxidative stress, and apoptosis post-SCI [87]. These findings highlight the therapeutic potential of miRNA modulation in SCI treatment.…”
Section: Targeted Therapies Modulating Microgliamentioning
confidence: 99%
“…As key regulatory factors of transcriptional gene expression changes in nervous system diseases, miRNAs have been widely concerned and studied by researchers ( 9 ). During SCI development, miRNA regulates neuronal plasticity, degeneration, axon regeneration, and myelin regeneration by changing gene expression ( 10 , 11 ). Research shows miR-940 decreases after SCI, and miR-940 overexpression inhibits inflammation and promotes functional recovery ( 12 ).…”
Section: Introductionmentioning
confidence: 99%